The effect of supplementation of liquid and crystalline lysine to barley-distillers solids diet on the performance and carcass quality of pigs - Valaja, Jarmo (Agricultural Research Centre of Finland, The Scientific Agricultural Society of Finland, The Finnish Society of Dairy Science, 1992)
Kasvatuskokeessa selvitettiin kiteisen tai nestemäisen lysiinilisäyksen vaikutusta ohra-tärkkelysrankkidieetillä ruokittujen lihasikojen tuotantotuloksiin sekä teuraslaatuun. Kokeessa oli 40 koe-eläintä, jotka jaettiin neljään kymmenen sian ryhmään ja kasvatettiin yksilöruokinnalla 25 kilon alkupainosta 95 kilon elopainoon. Neljä koerehua sisälsivät saman määrän nestemäistä tärkkelysrankkia ja ohraa ja niihin lisättiin joko nestemäistä tai kiteistä lysiiniä siten, että dieettien kokonaislysiinimääräksi tuli 7,1 tai 9,1 g lysiiniä/ry. Lisätyn puhtaan lysiinin määrä oli 0,9 tai 3,2 g/kg kuiva-ainetta. Nestemäisen tai kiteisen lysiinilisäyksen välillä ei havaittu eroja sikojen tuotantotuloksissa tai teuraslaadussa. Ainoastaan pitkän selkälihaksen poikkipinta-alassa oli ero kiteistä tai nestemäistä lysiiniä saaneiden eläinten välillä. Dieetin korkea lysiinitaso (9,1 g/ry) paransi selvästi sikojen päiväkasvua, rehuhyötysuhdetta ja teuras laatua verrattuna matalaan lysiini tasoon (7,1 g/ry). Leikkojen tuotantotulokset olivat hiukan paremmat kuin imisien, mutta imisien teuraslaatu oli kuitenkin selvästi parempi kuin leikkojen. Koe osoitti, että nestemäinen ja kiteinen lysiini ovat yhtä käyttökelpoisia sikojen ruokinnassa. Nestemäinen lysiini soveltuu hyvin liemiruokintaan täydentämään nestemäisiä viljaperäisiä valkuaisrehuja.

The response to dietary lysine of liquid or crystalline form was examined in pigs fed on cereal protein diets over the range of live weight from 25.0 to 95.0 kg. Forty individually fed growing pigs (20 gilts and 20 castrated males) were allocated to four isonitrogenous diets consisting of barley, undehydrated distillers solids and a mixture of minerals and vitamins with lysine supplementation of 0.9 or 3.2 9 pure lysine per kg DM in liquid or crystalline form to provide 7.1 or 9.1 g/FU total lysine, respectively. The pigs were given feed on a restricted scale twice dally. A high level of lysine supplementation significantly increased the growth rate and improved the feed conversion efficiency (p<0.001). A low level of lysine supplementation produced significantly less lean in carcass (p<0.05) and a smaller area of eye muscle (p<0.001). The loss at slaughter (in relation to live weight) of the pigs on high level of lysine supply was significantly lower than that of the pigs on low level of lysine supply (p<0.05). No significant differences were found in the performance and carcass quality of the pigs between liquid and crystalline form of lysine except that the area of eye muscle of the pigs on liquid lysine diets was larger than that of the pigs on crystalline lysine diets (p<0.05). No interaction was found between lysine source and level of supplementation on the performance or carcass quality. The results of this study showed that both sources of lysine supplementation were equally efficient 'm improving the performance of the pigs.
Keywords: Ko; lihasika; lysiini; rankki; kasvu; rehut; muuntosuhde; growing pigs; lysine; crystalline; liquid; distillers solids; performance; carcass quality